Analisis Faktor Risiko Terjadinya Stunting Di Wilayah UPTD Puskesmas I Denpasar Utara Kota Denpasar Provinsi Bali - Sugiani, Pande Putu Sri; Fanni, Lidya; -, Hendrayati (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2025)
Stunting is a very serious global problem. According to the WHO, the global stunting rate in 2022 will reach 148.1 million toddlers, or 22.3% of children under the age of five. In developing countries, children aged 0-5 are vulnerable to nutritional problems. Indonesia is one of the developing countries that has not yet been able to escape nutritional problems, including stunting. This type of research is an analytical observational study with a case-control study design. The case-control study begins by identifying the case group (stunting) and looking for a control group (not stunting). The conclusion in this study based on the results obtained a p-value of 0.756 (0.05) with a 1,467 times risk of stunting. Therefore, it can be concluded that there is no relationship between maternal age during pregnancy and the incidence of stunting.. In the results of this study there is no relationship between age during pregnancy with the incidence of stunting, this is supported by the frequency distribution in both groups which are equally high in the age group during pregnancy that is not at risk ( 20 years) which is 84.1% in the stunting toddler group while in the non-stunting group 88.6%. Maternal age during pregnancy does not have a significant relationship with the incidence of stunting p-value 1 ( 0.05). The results of this study show a p-value of 0.000 so it can be concluded that anemia is related to the incidence of stunting which is at the highest risk of 19,689 times stunting compared to mothers who are not anemic. In this study, a p-value of 0.001 (0.05) was obtained, it was concluded that the risk opportunity was 12,501 times stunting occurred, and it can be concluded that KEK is related to the incidence of stunting.